Folklore with Value Clarification Technique: Its Impact on Character Education of 8-9-Year-Old Students - Chairul Anwar; Antomi Saregar; Megawati Ridwan Fitri; Adyt Anugrah; Arifeen Yama (Journal of Innovation in Educational and Cultural Research, 2023)
Character education needs to be adequately integrated into classroom instruction. One method of implementing character education is using appropriate learning media and models. This study was conducted to describe the effect of qualitatively applying the Lampung folklore book â€œThe Legend of Tulung Nagaâ€ and the Value Clarification Technique (VCT) model in learning. The method used in this research is Single Subject Rate (SSR). The design of this study used A (baseline-1), B (intervention 1), A (baseline-2), and B (intervention 2). Based on the study results, the student's character developed after applying the Value Clarification Technique (VCT) model and Lampung folklore books in learning. This development can be seen in each stage of the research in stages A (baseline-1), B (intervention 1), A (baseline-2), and B (intervention 2). Based on observations and questionnaires, there is a strengthening of a religious character, nationalism, independence, cooperation, and integrity in students after reading Lampung folklore books and learning with the Value Clarification Technique (VCT) model. Based on the findings, it is possible to conclude that using story books in conjunction with the Value Clarification Technique model improves character education. This study adds knowledge about using the VCT model with learning material like legend storybooks to enhance students' character values.